Mediação familiar para idosos em risco: mapeamento de uma prática da promotoria de justiça cível do Foro Regional de Santo Amaro São Paulo (SP) - Martins, Alessandra Negrão Elias (2016)
Based on a positive understanding of conflict as something natural and inherent in human relationships, conflict isnow being addressed constructively. Resolution #125 passed by the Brazilian National Council of Justice as a Public Policy has increased access to Justice, such as the access to fair legal order, with the possibility of using appropriate conflict resolution methods including mediation. Several mediation methods are now in place. One such method is Transformative Mediation, which is based on interpersonal and family relationships, personal empowerment and recognition of the other. Today, this interdisciplinary method of mediation is being used in different contexts, such as the family. The mediator acts an impartial third party and as a facilitator of the communication between the conflicting parties. Within the context of the family, mediation can also be applied to elderly at risk. This is reflected on the concepts of family and aging that are unique to each person. Changes within the family have an impact on the care of children and dependent elderly. The Mediation Project for At-Risk Elderly was first introduced in 2011 as an initiative of the Civil Prosecutor s Office at the Regional District Court of Santo Amaro in the city of São Paulo to use mediation in family disputes through Administrative Proceedings forwarded to the Prosecutor's Office when elderly parents are at risk. As a rule, these elderly people are at risk due to moral and/or material abandonment. Typically, the mediation sessions are attended by the at-risk elderly, their family members, caregivers and cohabitants. The team of mediators consists of volunteer professionals who act as co-mediators and reflecting team. The results of the mediation cases conducted by the team were analyzed qualitatively. A few variables were taken into account, such as non-adherence to mediation and no significant changes between the parties after the mediation sessions, as well as the transformation of the conflict leading to an agreement between the parties and signing a memorandum of understanding, improvement in their communication, in the care of their elderly and their family life